Análise da eficácia dos mecanismos de autocicatrização do concreto - Pacheco, Fernanda (Universidade do Vale do Rio dos Sinos, 2020)
This research aimed to analyse four mechanisms of self-healing, by cement consumption, by pozzolans, by chemical and bacterial solutions. These compositions were submitted to water submersion cure and umid cure, also considering three conditions of exposition: reference, carbonation chamber and salt spray chamber. These traces were characterized by mechanical strength and fisical characteristics. Healing efficiency was assessed using a high-precision microscope. In addition, scanning electron microscopy (SEM) added to EDS and X-ray diffraction tests were performed. Pilot experiment were carried out, allowing to trace the growth curve of the bacterium B subtilis, and to compare perlite and clay as options for aggregates encapsulation. It was noticed that in the samples where cement consumption was evaluated, the exposure to carbonation may have affected the formation of healing productsProducts C-S-H, C-A-S-H and CaCO3 were formed. In samples with pozzolanic materials, it was noted that among the average values, the largest was 0.53 mm for continuous healing and 0.45 mm for punctual healing. Again, carbonation affected product formation. The same elements mentioned were identified in the DRX, in addition to products that make up the pozzolans used, such as SiO2, for example.In the samples containing chemical solutions, it is worth to notice that product occurs on the crack opening and also at sample surface. Among the products identified, there were C-S-H, CaCO3, SiO2 and CaO. Evaluating the samples containing bacterial solutions, in terms of the healing of fissures, a maximum 1.67 mm and maximum average of 1.48 mm countinuos healing was reached, demonstrating the potential of the technique. When analyzing the possibilities of submerged and moist healing, there was a balance between the number of occurrences. Assessing the impact of aggressive environments, it is worth noting that the presence of CO2 and Cl- did not affect the formation of healing. In terms of the identification of the products formed, it was noted the presence of calcite and C-S-H.
Keywords: Concreto autorregenerante; Durabilidade; Autocicatrização; Propriedades mecânicas; Self-healing concrete; Durability; Self-repairing; Mechanical properties; ACCNPQ::Engenharias::Engenharia Civil